The Effectiveness of Implementing Restorative Justice in Child Criminal Cases - Christina Bagenda; Ana Maria Gadi Djou; Agus Sugiarto; Andi Wahyuddin Nur; Ummi Kalsum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Restorative justice is an approach that is oriented towards resolving conflicts through dialogue between perpetrators, victims and the community. This approach provides an opportunity for perpetrators to understand the impact of their actions and take responsibility for their actions. Restorative justice is an approach to the justice system that focuses on recovery and rehabilitation, not punishment. This concept emphasizes dialogue between the perpetrator, victim and community to reach an agreement that benefits all parties. Restorative justice has emerged as a promising alternative, offering a different paradigm from the conventional justice system. This approach focuses on restoring relationships between perpetrators, victims, and society, and provides opportunities for perpetrators to understand the impact of their actions. The application of restorative justice in juvenile criminal cases shows significant potential in creating more positive outcomes for all parties involved. While challenges remain, steps to increase understanding and engagement of all parties can help optimize the effectiveness of this approach. Thus, restorative justice can be a valuable alternative in handling child criminal cases in Indonesia.